Para além da deliberação: desempenho dos conselhos de direitos na implementação de políticas para infância e adolescência em Goiás e no Distrito Federal (2012-2016) - Lozano, Renata Batista (2017)
Public policy councils exist in the structure of the Brazilian State with the function of controlling and deliberating the implemented actions. Faced with the exhaustion of political science literature regarding democratic deepening and gaps regarding the implementation of the policies managed by the councils, it is questioned to what extent the Councils of Rights of the Children and Adolescents of Goias and the Federal District have performed their functions for the implementation of policies foreseen by the Statute of the Child and Adolescent in the period from 2012 to 2016. The study was based on the analysis of Council documents verifying how the institutional design facilitates the implementation. The analysis of the resolutions of the State Council for the Rights of the Child and Adolescent of Goiás and of the District Council for the Rights of Children and Adolescents of the Federal District underwent the stage of categorization and analysis according to policies for children to identify relationships between institutional design, outputs and the impact on implementation. Finally, a methodology of comparative performance analysis was used, with criteria established according to the implementation literature, assigning performance values (High Performance DEA, Medium Effective Performance - DEM and Low Effective Performance - DEB) applied to each one of the Councils to measure analytically the productivity of these councils with regard to the implementation of ECA policies. In summary, we can affirm that the results obtained indicate that the CEDCA-GO has a low performance in the impact of the implementation of these policies, while the CDCA-DF has a higher performance in the implementation.